Management of Iron-Deficiency Anemia on Inpatients and Appropriate Discharge - Ali Zulqar Nain, Ambreen Sehar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Anaemia is a condition in which the number of red blood cells is insufficient to meet physiologic needs; it is caused by many conditions, particularly iron deficiency. Aims and objectives: The main objective of the study is to analyse the management of iron-deficiency anemia on inpatients and appropriate discharge. Material and methods: This cross sectional study was conducted in DHQ hospital Sheikhupura with the permission of ethical committee of hospital. Data were collected from 100 patients. Participants were selected through randomly sampling technique. Iron deficiency criterion for men was defined as hemoglobin under 13 g/dL, and women under 12 g/dL, with ferritin less than 30 ng/dL for any patient. Diagnostic criteria in patients with congestive heart failure were ferritin below 300 ng/dL and transferrin saturation (TSAT) under 20%. Results: The data was collected from 103 patients. The only factors which emerged as statistically significant from the adjusted logistic regression analysis model were insufficient intakes of iron (OR = 7.39; 95% CI: 1.45-37.57) and vitamin C (OR = 6.14; 95% CI: 1.34-28.27), frequent (≥2 times per week) tea consumption (OR = 0.01; 95% CI: 0.01-0.08), infrequent (≤2 times per week) red meat consumption (OR = 3.71; 95% CI: 1.01-13.61), and the possession of a personal history of IDA (OR = 6.00; 95% CI: 1.45-24.76). Conclusion: It is concluded that Iron-deficiency anemia is also tricky in patients with chronic diseases. Iron supplementation has been shown to help reduce mortality in those with blood loss.